An expert knowledge based decommissioning alternative selection system for fixed oil and gas assets in the South China Sea. (15th January 2017) - Na, K.L.; Lee, H.E.; Liew, M.S.; Wan Abdullah Zawawi, N.A.
Abstract: The decommissioning process is constantly challenged with indeterminate risks associated with deteriorated structures and the practice of late-life decommissioning planning. The issue is further complicated by the absence of a fit-for-purpose decision framework. This work develops a knowledge based advisory expert system to address the late-life structural ambiguity of fixed jacket platforms in the selection of a best practicable decommissioning method. A review on the decommissioning industry and its growing need for data-driven management are presented. Analytic Hierarchy Process (AHP) is utilized to solve the Multi-Criteria Decision Making (MCDM) problem of choosing the best practicable decommissioning alternative. The effects and ranking of identified key structural-operation factors on the decommissioning planning process are numerically computed and discussed. The key system variables are developed with reference to established Asset Integrity Management Systems. Subject matter expert surveys are conducted on leading decommissioning and structural integrity experts in the region which are reflected in the decision matrices. A mathematical standardization technique is employed to remove inconsistencies in the intermediate decision vectors. The model is benchmarked against an actual decommissioning project in Malaysian waters which was based on conventional practices. A comprehensive framework is proposed to establish a practical working philosophy for the developed algorithm. Highlights: An expert knowledge based model for the most feasible decommissioning alternative from a techno-operation standpoint. A preliminary screening algorithmic framework is presented to conceptualize an effective database management system. The study concluded with a benchmark decommissioning case study of a steel monopod platform in the South China Sea.